The role of homeopathy in the treatment of asthma: A literature review (International Seven Journal of Health Research, 2024)
The aim of this article is to characterize Homeopathy, describe the pathology of asthma and explain, based on a literature review, the positive or negative health impacts of using Homeopathy as an adjunct to traditional asthma treatment. The research was carried out by searching for scientific productions in the Pubmed database, inserting the following MeSH descriptors: "Asthma"; "Homeopathy". These terms were then translated into medical vocabulary and the following expressions were found: Homeopathy ; Asthmas and Bronchial Asthma. The Boolean operator "OR" was used between combinations relating to Asthma and the operator AND between combinations relating to Asthma and Homeopathy. The inclusion criteria were articles related to the descriptors selected, which agreed with the theme of the study, published between 2013 and 2023, using the filters: "full and free text" and "10 years", the latter referring to the date of publication of the articles searched. A total of 14 articles were found in English and Spanish, and after reading the titles and abstracts, 3 were excluded for evading the proposed theme. It is worth noting that 9 of the 11 articles studied question the veracity of the use of homeopathy in the treatment of asthma. It is therefore worth discussing the effectiveness of Homeopathy in the treatment of asthma and its use. This article has brought contrary references, which shows the existence of a controversy in relation to the use of Homeopathy in the current century. It is undeniable that non-traditional medicine has many benefits and has been growing in the country, which is why it needs to be presented to health professionals and patients as a therapeutic option. With this, it is clear that there is a need for more studies on Homeopathy and other integrative practices, greater inclusion of these practices in the Unified Health System, as well as greater inclusion of them in Brazilian medical education in order to demystify untrue information about this important science. Homeopathy is the most widely used complementary and integrative therapy in the treatment of asthma today, but scientific studies need to be continually developed in order for it to be recognized and disseminated as a therapy that promotes safe and lasting cures.